Oxytetracycline and paracetamol biodegradation performance in the same enriched feed medium with aerobic nitrification/anaerobic denitrification SBR - Celik, Aytekin (Springer, 2021)
Pharmaceuticals such as oxytetracycline and paracetamol are extensive chemicals in the aquatic systems. In this study, the removal performance of oxytetracycline and paracetamol was investigated in the same enriched feed water medium by sequencing batch aerobic/anaerobic reactor system. In this context, oxytetracycline and paracetamol in the aerobic phase were removed by a maximum of 66 and 99.8% respectively. At the same time, nitrification and denitrification removals were obtained as 95% and 98%, respectively. On the other hand, oxytetracycline and equivalent O-2 flux of oxytetracycline maximum were calculated as 1.18 and 2.14 mg/L.d and the maximum removal volumetric flux of paracetamol and its O-2 equivalent flux were determined approximately as 136 and 303 mg/L.d, simultaneously. In addition, oxytetracycline and paracetamol were given to the system in an amount of maximum 1 and 500 mg/L, respectively. Paracetamol has not significantly affected nitrification and denitrification up to 120 mg/L, but 500 mg/L paracetamol has completely finished denitrification in this system. On the other hand, the water environment of sequencing batc reactor has turned into a pitch dark state at 500 mg/L paracetamol feeding. As a result, aerobic bacteria preferred paracetamol rather than oxytetracycline. In other words, aerobic bacteria preferred paracetamol/oxytetracycline as the second electron acceptor after O-2.
Keywords: Denitrification; Nitrification; Oxytetracycline; Paracetamol; Sequencing batch reactor